THE EFFECTIVENESS OF THE ‘INGAT PESAN IBU’ CAMPAIGN IN CHANGING LATE ADOLESCENT BEHAVIOR IN THE TOURISM AREAS OF BALI, BANDUNG, AND YOGYAKARTA - Gusanti, Amelia Dwinda; Larasati, Berlian Syarafina; Putra Cahayaning Tyas, Nathanael Khareza; Sianipar, Grace Hanny; Wulan, Roro Retno (International Journal of Research -GRANTHAALAYAH, 2022)
The high number of Covid-19 cases in Indonesia has prompted the government to promote various efforts to suppress the spread of Covid-19 cases, one of which is ‘Ingat Pesan Ibu’ campaign. However, several tourism areas such as Bali, Bandung, and Yogyakarta are still favourite tourism destinations in the pandemic era. This research was conducted to determine if the ‘Ingat Pesan Ibu’ campaign effectively changes late-adolescents’ behavior and determine how far is the late adolescents receive ‘Ingat Pesan Ibu’ campaign in Bali, Bandung, and Yogyakarta. The method used is quantitative descriptive includes table of mean, standard deviation and being analyzed descriptively according to data’s tendency. Pearson Product Moment formula is used for validity test and Cronbach Alpha formula for reliability test. Kolmogorov-Smirnov formula is used for normality test before doing the T-test. In each region, the T-test shows Sig. (2-tailed) is greater than 0.1, which means ‘Ingat Pesan Ibu’ campaign effectively changed late-adolescent behavior. The campaign is effective on Knowledge (X1), Attitudes (X2), and Skills (X3) variables with a mean above 3.5. The behavior (X4) stage is not optimal because the mean result is still at number 3, supported by variable X4.4 which shows answers about taking-off masks in public spaces.